First record of Hexathrombium (Acari: Microtrombidiidae) on Tetracha (Tetracha) brasiliensis brasiliensis (Coleoptera: Cicindelidae) in Argentina - Almada, Melina Soledad; Cédola, Claudia (Systematic & Applied Acarology Society, 2021)
Mites of the genus Hexathrombium Cooreman were collected from Tetracha (Tetracha) brasiliensis brasiliensis (Cicindelidae) in Bt cotton crops. This is the first record of this mite in Argentina.